Advancing early detection of organ damage and cardiovascular risk prevention: the Suzhou cardiometabolic health study protocol - exploring the role of oral microbiome and metabolic profiling in risk stratification - Zhu, Mengmeng; Li, Yiwen; Wang, Wenting; Liu, Longkun; Liu, Wenwu; Yu, Jiayu; Xu, Qian; Cui, Jing; Liu, Yanfei; Chen, Keji; Liu, Yue (Frontiers in Endocrinology, 2025)
BackgroundCardiovascular Disease (CVD) is the leading cause of global mortality, with its incidence rate rising year by year due to the prevalence of metabolic diseases. Existing primary and secondary prevention strategies for cardiovascular disease have limitations in identifying some high-risk groups, and 1.5-level prevention aims to achieve more precise intervention by early identification of subclinical target organ damage. This study introduces oral (tongue coating) microbiota as metabolic markers for the first time, in combination with multiple metabolic factors, to explore their potential in assessing subclinical target organ damage and optimizing cardiovascular risk stratification, in order to provide a new path for the early identification and intervention of CVD.MethodsThis study is a prospective cohort study aimed at assessing the association between tongue coating microbiota characteristics and multiple metabolic factors with subclinical target organ damage, and identifying high-risk groups suitable for cardiovascular 1.5-level prevention. The study will be conducted in Suzhou City, Jiangsu Province, China, planning to include 5000-6000 eligible subjects, with inclusion criteria of age ≥18 years, excluding individuals with a history of CVD and other serious diseases. Baseline assessment includes demographic information, lifestyle (including dietary patterns), medical history, physical examination, and collection of tongue coating microbiota samples. Subjects will be followed up every 2 years, with the primary outcome being the first occurrence of coronary heart disease and stroke, and the secondary outcome being subclinical target organ damage.DiscussionThis study focuses on cardiovascular 1.5-level prevention strategy, combining metabolic factors with tongue coating microbiota characteristics, aiming to optimize the risk assessment system for subclinical target organ damage. This approach can not only fill the gap in traditional risk assessment but also provide new ideas for the early identification and intervention of CVD. In the future, the feasibility and effectiveness of this strategy will be verified through multicenter studies, and it is expected to be promoted to a wider medical system, significantly improving the health management level of high-risk groups for CVD.Trial registration numberhttp://itmctr.ccebtcm.org.cn, identifier ITMCTR2024000616.